The invasion process of the entomopathogenic fungus Ophiocordyceps sinensis into the larvae of ghost moths (Thitarodes xiaojinensis) using a GFP-labeled strain - Wu, Peipei; Qin, Qilian; Zhang, Jihong; Zhang, Huan; Li, Xuan; Wang, Hongtuo; Meng, Qian (Frontiers in Microbiology, 2022)
Chinese cordyceps is a well-known and valuable traditional Chinese medicine that forms after Ophiocordyceps sinensis parasitizes ghost moth larvae. The low natural infection rate of O. sinensis limits large-scale artificial cultivation of Chinese cordyceps, and the invasion process is unclear. To investigate the temporal and spatial regulation when O. sinensis enters ghost moths, we constructed an O. sinensis transformant that stably expresses green fluorescent protein (GFP). Inoculating Thitarodes xiaojinensis larvae with a high concentration of GFP-labeled O. sinensis, we observed that O. sinensis conidia could adhere to the host cuticle within 2 days, germinate penetration pegs within 4 days, and produce blastospores in the host hemocoel within 6 days. The reconstructed three-dimensional structures of the invasion sites showed that penetration pegs germinated directly from O. sinensis conidia at the joining site with the larval cuticle. Differentiated appressoria or hyphae along the host epicuticle are not required for O. sinensis to invade ghost moths. Overall, the specific invasion process of O. sinensis into its host is clarified, and we provide a new perspective on the invasion process of entomopathogenic fungi.